2010
DOI: 10.1097/yic.0b013e3283311acd
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacological properties of antidepressants

Abstract: Antidepressant drugs represent one of the main forms of effective treatment for the amelioration of depressive symptoms. Most available antidepressants increase extracellular levels of monoamines. However, it is now recognized that monoamine levels and availability are only part of the story, and that antidepressants whose mechanism of action is mainly based on the modulation of monoaminergic systems may not be able to satisfy the unmet needs of depression. Therefore, a number of compounds, developed for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 227 publications
(231 reference statements)
0
45
0
Order By: Relevance
“…This disease is a chronic mental disorder, and in some cases, is a potentially fatal disorder, representing a serious public health problem that generates high costs to society (Fleck et al, 2009) and that strongly affects quality of life of the patients (Larsen et al, 2010;Van Der Feltz-Cornelis et al, 2010). It is wellestablished that depression involves a reduction in the monoamine system, particularly in the neurotransmission of serotonin, dopamine and norepinephrine, or impaired activity of their receptors (Racagni and Popoli, 2010). In summary, the center of action of current drug therapy is to correct monoamine deficits by increasing synaptic concentrations (Higgins and George, 2010;Bennabi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This disease is a chronic mental disorder, and in some cases, is a potentially fatal disorder, representing a serious public health problem that generates high costs to society (Fleck et al, 2009) and that strongly affects quality of life of the patients (Larsen et al, 2010;Van Der Feltz-Cornelis et al, 2010). It is wellestablished that depression involves a reduction in the monoamine system, particularly in the neurotransmission of serotonin, dopamine and norepinephrine, or impaired activity of their receptors (Racagni and Popoli, 2010). In summary, the center of action of current drug therapy is to correct monoamine deficits by increasing synaptic concentrations (Higgins and George, 2010;Bennabi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…1) that inhibits 5-hydroxytryptamine (serotonin) and norepinephrine reuptake [7]. Imipramine is one of the most effective drugs in the treatment of severe chronic depression [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, these drugs have significant limitations, including a long time lag for therapeutic response (weeks to months), low response rates and side effects serious enough to induce discontinuation in nearly 20% of patients. Moreover, the delayed response is suggestive of an involvement in antidepressant therapeutic action of slow-onset adaptations in downstream signaling pathways regulating neuroplasticity and cellular resilience [2,3].…”
Section: Editorialmentioning
confidence: 99%
“…However, these drugs have significant limitations, including a long time lag for therapeutic response (weeks to months), low response rates and side effects serious enough to induce discontinuation in nearly 20% of patients. Moreover, the delayed response is suggestive of an involvement in antidepressant therapeutic action of slow-onset adaptations in downstream signaling pathways regulating neuroplasticity and cellular resilience [2,3].Recent growing evidence suggests that glutamatergic neurotransmission, the major excitatory system in the brain, plays a critical role in the pathophysiology and treatment of neuropsychiatric disorders. The glutamatergic system is interconnected with GABAergic and monoaminergic pathways, and it has been shown that approximately 80% of neurons in the neocortex are excitatory glutamatergic neurons [4].…”
mentioning
confidence: 99%